2009
DOI: 10.1371/journal.ppat.1000450
|View full text |Cite
|
Sign up to set email alerts
|

Vpu Antagonizes BST-2–Mediated Restriction of HIV-1 Release via β-TrCP and Endo-Lysosomal Trafficking

Abstract: The interferon-induced transmembrane protein BST-2/CD317 (tetherin) restricts the release of diverse enveloped viruses from infected cells. The HIV-1 accessory protein Vpu antagonizes this restriction by an unknown mechanism that likely involves the down-regulation of BST-2 from the cell surface. Here, we show that the optimal removal of BST-2 from the plasma membrane by Vpu requires the cellular protein β-TrCP, a substrate adaptor for a multi-subunit SCF E3 ubiquitin ligase complex and a known Vpu-interacting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

61
491
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(555 citation statements)
references
References 58 publications
61
491
3
Order By: Relevance
“…2E). In general, our results corroborate those reported in several recent manuscripts (27,32,35), which have each found that the two cytosolic lysines have no phenotype with respect to viral egress or surface down-regulation by Vpu. However, as described above, disagreement remains regarding the contribution that these lysines make toward Vpu-dependent ubiquitination.…”
Section: Vpu-dependent Bst-2 Ubiquitinationsupporting
confidence: 92%
“…2E). In general, our results corroborate those reported in several recent manuscripts (27,32,35), which have each found that the two cytosolic lysines have no phenotype with respect to viral egress or surface down-regulation by Vpu. However, as described above, disagreement remains regarding the contribution that these lysines make toward Vpu-dependent ubiquitination.…”
Section: Vpu-dependent Bst-2 Ubiquitinationsupporting
confidence: 92%
“…The mechanism of tetherin inhibition remains incompletely characterized but again, there are clearly significant mechanistic differences between the various viral antagonists. HIV-1 Vpu appears to lead to a reduction of steady-state tetherin levels (6,7,9) and exclusion from sites of particle assembly at the plasma membrane (2,26). Recent data suggest that Nef may remove tetherin from the cell surface (3) as it does other cell surface molecules (27).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have suggested that Vpu expression leads to tetherin degradation (6,7,9). We therefore examined the impact of SIVtan envelope expression on tetherin levels.…”
Section: Sivtan Env Does Not Reduce Total Tetherin Levels But Depletesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tetherin antagonism by Vpu also depends in part on the recruitment of βTrCP-2, an adaptor protein for an E3 ubiquitin ligase involved in targeting tetherin for degradation (24,25,30,31). Hence, substitutions in a conserved DSGxxS motif in the cytoplasmic tail of Vpu (S52,56N) that prevent the recruitment of βTrCP-2 partially impair tetherin antagonism by preventing its degradation, but not its endosomal sequestration (25,(30)(31)(32)(33). These substitutions are also known to abrogate CD4 down-regulation, but do not affect Vpu-mediated down-modulation of NTB-A (23).…”
Section: Deletion Of Vpu Increases the Susceptibility Of Hiv-1-infectmentioning
confidence: 99%